Protocol of a study to benchmark occupational health and safety in Japan: W2S-Ohpm study - Nagata, Tomohisa; Odagami, Kiminori; Nagata, Masako; Adi, Nuri Purwito; Mori, Koji (Frontiers in Public Health, 2023)
We aim to conduct a prospective cohort study to benchmark occupational health and safety in Japan. Here, we describe the detailed protocol for the baseline survey based on the Checklist for Reporting Results of Internet E-Surveys. We conducted the baseline survey for the prospective cohort study in 2022. Our target population was workers in Japan aged 20 years or older, who we sampled to be representative of the Japanese workforce, stratified by sex, age, and region. Among 59,272 registered monitors who answered the initial screening questions, 29,997 completed the survey. After excluding 2,304 invalid responses, we used 27,693 valid participants in our final analysis. The number and mean age of men were 15,201 (55%) and 46 years; those of women were 12,492 (45%) and 45 years. With respect to sex, age, and regional composition, our sampling was representative of Japan's working population. Our sampling for employment status and industry yielded almost the same proportions as a government-led representative sampling of workers in Japan.